Gastropleural fistula following pulmonary resection. Issue 12 (December 1993) - O'Keefe, P A; Goldstraw, P
Abstract : A 77 year old man with an eight month history of polymyalgia rheumatica treated by steroids underwent left lower lobectomy for a non-small cell carcinoma. Following discharge he developed a pneumothorax, empyema, septicaemia, and acute renal failure. Reinvestigation and reoperation showed this to be caused by a non-malignant non-traumatic direct gastropleural fistula.